[OP.8A.01] NEWLY DIAGNOSED DIABETES MELLITUS IS ASSOCIATED WITH INCREASED LEVELS OF ERYTHROCYTE MICROPARTICLES. (September 2017) - Gkaliagkousi, E.; Nikolaidou, B.; Giannaki, E.; Markala, D.; Samalidou, A.; Triantafyllou, A.; Vamvakis, A.; Gavriilaki, E.; Douma, S.
Abstract : Objective: Patients with Diabetes Mellitus (DM) carry a high burden of cardiovascular damage and high risk of early thrombotic events. It is currently unknown how early this damage occurs and if it preexists in naive newly diagnosed DM patients. Design and method: We sought to determine the thrombotic tendency of patients with known cardiovascular risk factors. To this end we used sophisticated, novel markers of atherosclerotic and thrombotic damage: platelet (PLTs) and erythrocyte (RBCs) microparticles. Consecutive patients of the Micro- and Macro-vascular disease Clinic of Third Department of Internal Medicine at Papageorgiou General Hospital of Thessaloniki were included in the study. A thorough medical history was taken and a blood sample was drawn. A 24-hour urine collection was performed to assess the presence of microalbuminuria. Furthermore, PLTs and RBCs were determined using flow cytometry according to specific protocol. Cardiovascular risk factors were evaluated with emphasis on hypertension, newly diagnosed DM, dyslipidemia, smoking and body mass index. Results: Our study sample consisted of 45 patients aged 52.5 ± 11.9 years, 19 men: 26 women, with mean systolic / diastolic blood pressure: 132.7 ± 16.8 / 83.3 ± 13.7 mmHg. Newly-diagnosed DM was found in 19 patients, while untreated hypertension in 16. Multiple linear regression analysis showed that DM makes the strongest contribution to high RBCs values (beta: 0, 673, p = 0, 021) after the effect of cardiovascular risk factors is controlled for. No significant predictor of PLTs could be identified. Conclusions: In our study, RBCs strongly correlated with the presence of DM at the very early stages of the disease, despite the small sample size. Current knowledge suggests that RBCs consist a robust indicator of thrombotic tendency. The fact that PLTs did not correlate with the presence of DM in our study may, at least in part, reflect the multifactorial role of platelets not only in the thrombotic but also in the inflammatory process of atherosclerosis. Larger studies are needed to determine the value of PLTs and RBCs in patients with cardiovascular risk factors.